Implikasi Ketiadaan Guru Pendamping terhadap Perkembangan Emosional Anak Usia Dini di PAUD - Siti A Bidjuni; Nurainun Pandju; Sri A Onde; Wayan Indriani; Davina S Maladjai (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
Early Childhood Education (PAUD) is a crucial stage in children's cognitive, social, and emotional development. The role of accompanying teachers in the PAUD environment is very important to support an effective and conducive learning process. Accompanying teachers contribute to the planning, implementation, and evaluation of learning activities, as well as helping to manage heterogeneous classrooms. However, the limited number of accompanying teachers in some schools, with a ratio of 1 teacher to 15 children, can hinder the effectiveness of learning. This condition makes the main teacher face challenges in providing individual attention, especially to children who need additional support. This study highlights the positive impact of the presence of accompanying teachers on children's emotional stability, learning time efficiency, and more optimal learning outcomes. The presence of accompanying teachers also allows the implementation of structured play activities, more targeted social interaction, and continuous monitoring of children's development. Thus, the existence of accompanying teachers is a key factor in creating a learning environment that supports children's growth and development holistically, while improving the quality of educational services in early childhood education institutions.